Secure data aggregation in IoT using Efficient-CSDA - Swathi S; Yogish H K (Institute of Advanced Engineering and Science, 2019)
In recent days, IoT has been widely accepted and WSN (Wireless Sensor network) is being used for variety of the applications such as transportation, medical, environmental, military, it moreover the main aim to deploy the WSN is to collect the data about the given set of phenomena. The common task of WSN is to sense the data and send over the network. Moreover, due to the various purpose such as statistical analysis, the data aggregation is required. However, the when the dynamic network topology is considered, it is considered to be the very difficult task to provide the secure and efficient data aggregation. The main issue here is to ensure the security and accuracy of the data aggregation. Hence, in this research we have proposed an algorithm named as E-SDA (Efficient Secure Data Aggregation) in order to provide the secure data. In this, the algorithm provides the flexibility to detect the dishonest honest through neighbor monitoring. Later, extensive simulation has been done in order to prove the convergence of our algorithm.